Non-price criteria for the evaluation of the tender offers in public procurement of Ukraine - Alexander Baranovsky; Nataliia Tkachenko; Vladimer Glonti; Valentyna Levchenko; Kateryna Bogatyrova; Zaza Beridze; Larisa Belinskaja; Iryna Zelenitsa (International Journal of Financial Studies, 2020)
Traditionally, public procurement has been associated with the measurement of achieving savings. However, recent research shows that the economic impact of public procurement is not limited only to savings, but by measuring the impact of four capitals-natural, human, social, and economic-on sustainable well-being over time. Ukraine is a country with a very low gross domestic product (GDP) per capita, which exacerbates the problem of the impact of public procurement results on the population's welfare. Ukrainian public procurement legislation allows customers to apply non-price criteria (the share of non-price criteria cannot be more than 70%), which, together, are taken into account in the formula of the quoted price. The studies show that the effect of the use of non-price criteria depends on the relevance of the method of the evaluation of non-price criteria. The most important non-price criteria for Ukrainian customers by product categories and the methods of their evaluation are analyzed according to the Bi.prozorro.org analytics module. Therefore, it is concluded that the quoted price method, which is used in Ukrainian practice, is not relevant in comparison with the method used in the EU. A survey of the government buyers on the practice of applying non-price criteria was conducted, and the areas of their use were identified.
Keywords: 330; public procurement; evaluation of tender offers; non-price criteria; life cycle cost; quoted price